Some aspects of digitalization on public administration - Imanbekova, A.M.; Fyliuk, Н.М.; Stavbunik, E.A. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
Abctract Object: Public administration's digital transformation is examined in this paper. The study's goal is to better understand how public administration organizations are changing in order to streamline administrative decision-making procedures. Methods: This study examines the effects of digitization on public administration systems through an interdisciplinary approach that offers an evaluation of socio-economic processes. The organizational features of Kazakhstan's public administration's digitization are the study's focus. Findings: The writers of the suggested scientific work provide the primary directions of public administration's digital transformation while concentrating on the key components of the concept of “digitalization of public administration” and analyzing the key indicators of this process in Kazakhstan. Conclusions: In the contemporary digital era, the delivery of public services should remain centered on meeting the requirements of citizens and businesses. Simultaneously, digitalization introduces novel tools and procedures that streamline and enhance the convenience, accessibility, comprehensibility, and safety of traditional approaches.
Мемлекеттік басқаруды цифрландырудың кейбір аспектілері
Некоторые аспекты цифровизации государственного управления
Keywords: Public administration's digital transformation; the number of fixed Internet subscribers; the population's degreeof digital literacy; electronic public services